Voluntary Peer Review of Competition Law and Policy - Bangladesh - United Nations Conference on Trade; Development (United Nations, 2022)
United Nations Conference on Trade and Development (UNCTAD) voluntary peer reviews of competition law and policies are conducted at annual meetings of the Intergovernmental Group of Experts on Competition Law and Policy or at five-yearly United Nations Conferences to Review the United Nations Set. The substantive preparation was carried out by the Competition and Consumer Policies Branch (CCPB) of UNCTAD under the direction of Teresa Moreira, Head of CCPB. This report was prepared for UNCTAD by Maria Leonila Papa. The substantive backstopping and review of the report was the responsibility of Dr. Pierre Horna and Elizabeth Gachuiri, assisted by Hyejong Kwon, Competition and Consumer Policies Branch, under the guidance of Teresa Moreira, Head of the Branch, UNCTAD. Elona Lazaj assisted in coordinating the process with the Bangladesh Competition Commission and the consultant as part of the UNCTAD team for the Bangladesh peer review on competition policy.